The fugu plan : - Tokayer, Marvin (Paddington Press Ltd., 1979)
The Japanese studied the book and, according to all accounts, naively believed its propaganda. Their reaction was immediate and forceful – they formulated a plan to encourage Jewish settlement and investment into Manchuria. People with such wealth and power as the Jews possess, the Japanese determined, are exactly the type of people with whom we want to do business!. The Japanese called their plan for Jewish settlement "The Fugu Plan." The "fugu" is a highly poisonous blowfish. After the toxin-containing organs are painstakingly removed, it is used as a food in Japan, and is considered an exquisite delicacy. If it is not prepared carefully, however, its poison can kill a person.